Metabarcoding analysis of oral microbiome during pregnancy - Benslimane, Fatiha M.; Mohammed, Layla I.; Abu-Hijleh, Haya; Suleiman, Sara; Boughattas, Sonia; Zakaria, Zain Zaki; Fthenou, Eleni; Al-Asmakh, Maha (Frontiers in Cellular and Infection Microbiology, 2024)
Pregnancy is a dynamic physiological process involving significant hormonal, immune, and metabolic changes to support fetal growth and development. This study investigates the changes in salivary microbiome and biochemical markers from the second to the third trimester of pregnancy. Saliva samples were collected from 45 pregnant women enrolled in the Qatar Birth Cohort study at two time points (second and third trimesters). DNA was extracted and subjected to 16S rRNA gene sequencing using Oxford Nanopore Technology. Microbial diversity and taxonomic analyses were performed, along with correlation analyses between microbial abundance and clinical parameters. Biochemically, significant increases in BMI, pulse rate, HbA1c, LDL, total cholesterol, and triglycerides were observed in the third trimester compared to the second. Microbial diversity analysis revealed significant changes in microbial richness and composition. Taxonomy analysis showed a significant 3-fold increase in Bacteroidota. Also, a significant decline in Selenomonas and a significant increase in Veillonella, specifically Veillonella dispar and Veillonella atypica, as well as an increase in Granulicatella were observed in the third trimester, along with a significant decrease in Streptococcus sanguinis. Correlation analysis during the second trimester revealed positive associations between BMI, cholesterol, LDL, and Selenomonas, and negative correlations with Streptococcus and Gemella. In the third trimester, BMI was negatively correlated with Campylobacter, glucose levels were negatively correlated with Neisseria, and triglyceride levels were negatively correlated with Prevotella. These findings highlight significant biochemical and microbial shifts during pregnancy, underscoring the importance of monitoring oral health and metabolic changes in pregnant women.